Oral administration of Chinese herbal medicine during gestation period for preventing hemolytic disease of the newborn due to ABO incompatibility: A systematic review of randomized controlled trials. - Huijuan Cao; Ruohan Wu; Mei Han; Patrina Ha Yuen Caldwell; Jian-Ping Liu (PLoS ONE, 2017)
About 85.3% of hemolytic disease of the newborn (HDN) is caused by maternal-fetal ABO blood group incompatibility. However, there is currently no recommended "best" therapy for ABO incompatibility during pregnancy.To systematically assess the safety and effectiveness of oral Chinese herbal medicine (CHM) for preventing HDN due to ABO incompatibility.The protocol of this review was registered on the PROSPERO website (No. CRD42016038637).Six databases were searched from inception to April 2016. Randomized controlled trials (RCTs) of CHM for maternal-fetal ABO incompatibility were included. The primary outcome was incidence of HDN. The Cochrane risk of bias tool was used to assess the methodological quality of included trials. Risk ratios (RR) and mean differences with 95% confidence interval were used as effect measures. Meta-analyses using Revman 5.3 software were conducted if there were sufficient trials without obvious clinical or statistical heterogeneity available.Totally 28 RCTs involving3413 women were included in the review. The majority of the trials had unclear or high risk of bias. Our study found that the rate of HDN and the incidence of neonatal jaundice might be 70% lower in the herbal medicine group compared with the usual care group (RR from 0.25 to 0.30).After treatment with herbal medicine, women were twice as likely to have antibody titers lower than 1:64 compared with women who received usual care(RR from 2.15 to 3.14) and the umbilical cord blood bilirubin level in the herbal medicine group was 4umol/L lower than in those receiving usual care. There was no difference in Apgar scores or birthweights between the two groups.This review found very low-quality evidence that CHM prevented HDN caused by maternal-fetal ABO incompatibility. No firm conclusions can be drawn regarding the effectiveness or safety of CHM for this condition.